Factors influencing entrepreneurial intentions among the students in the Baltic Sea region countries - Stabingis, Linas; Raupelienė, Asta (Business: Theory and Practice, 2023)
This research presents a comparison of the impact of personal and environmental factors on the entrepreneurial intention of students living in Baltic Sea region countries. Data on students’ intentions to start their own businesses was obtained from 10054 respondents studying in Estonia, Finland, Lithuania, Poland, and Sweden by implementing Global University Entrepreneurial Spirit Students’ Survey (GUESSS) in 2021. Data analysis was conducted using modified Krueger’s (2009) entrepreneurial intention model based on the Theory of Planned Behaviour (TPB). Six hypotheses were tested using the data received from all respondents and the data of individual sub-samples broken down by gender, level of study, the field of study, and country of residence. A positive relationship with students’ entrepreneurial intentions was clarified and the selected hypotheses were proved by analysing all variables of all sub-samples, except for three in the case of Lithuania and two in the case of Sweden and Finland due to insufficient level of statistical significance.